An assessment of social vulnerability to climate change among the districts of Arunachal Pradesh, India. (June 2017) - Maiti, Sanjit; Jha, Sujeet Kumar; Garai, Sanchita; Nag, Arindam; Bera, A.K.; Paul, Vijay; Upadhaya, R.C.; Deb, S.M.
Abstract: The present study highlighted the state of climate change induced social vulnerability of the districts of Arunachal Pradesh. For the purpose of assessment of one of the most fragile ecosystems of the eastern Himalaya, the 'Integrated Vulnerability Assessment Approach' and IPCC's definition of vulnerability were utilized. The assessment was based on various secondary data, like socio-economic and biophysical indicators, collected from several authenticated sources; and the respective weightage of these indicators was assigned by using 'Principal Component Analysis'. Vulnerability was calculated as the net effect of exposure and sensitivity on the adaptive capacity. Anjaw district of eastern Arunachal Pradesh was found to be the most vulnerable district, while Tawang district of western Arunachal Pradesh happened to be the least vulnerable. This net effect was found negative in 7 out of 12 districts viz. Anjaw, Upper Siang, West Siang, Lower Dibang Valley, East Siang, East Kameng and Kurung Kurmey. This net negative effect could be construed as an alarming situation.